2012
DOI: 10.1007/s10059-012-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Localization of Glycogen Synthase Kinase 3β Is Required Its Putative PY-Nuclear Localization Sequences

Abstract: Glycogen synthase kinase-3β(GSK-3β), which is a member of the serine/threonine kinase family, has been shown to be crucial for cellular survival, differentiation, and metabolism. Here, we present evidence that GSK-3β is associated with the karyopherin β2 (Kap β2) (102-kDa), which functions as a substrate for transportation into the nucleus. A potential PY-NLS motif ( 109 IVRLRYFFY 117) was observed, which is similar with the consensus PY NLS motif (R/K/H)X 2-5 PY in the GSK-3β catalytic domain. Using a pull do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…Intracellular localization is controlled at different regulatory levels [12]. These include (de-)phosphorylation [67], association with proteins facilitating nuclear import (e.g., karyopherin β2 [68] or herpesvirus-derived latency-associated nuclear antigen (LANA) [69]) or export (e.g., GSK3-binding protein [70]), and partial digestion (see Section 2.2.3). Recently, it has been shown that inactivation of the phosphatidylinositol-3-kinase (PI3K), protein kinase B (PKB/Akt), mechanistic target of rapamycin complex (mTORC) 1 axis results in the nuclear accumulation of both GSK3α and β.…”
Section: Gsk3 Proteins-paralogs Isoforms Expression and Localizationmentioning
confidence: 99%
“…Intracellular localization is controlled at different regulatory levels [12]. These include (de-)phosphorylation [67], association with proteins facilitating nuclear import (e.g., karyopherin β2 [68] or herpesvirus-derived latency-associated nuclear antigen (LANA) [69]) or export (e.g., GSK3-binding protein [70]), and partial digestion (see Section 2.2.3). Recently, it has been shown that inactivation of the phosphatidylinositol-3-kinase (PI3K), protein kinase B (PKB/Akt), mechanistic target of rapamycin complex (mTORC) 1 axis results in the nuclear accumulation of both GSK3α and β.…”
Section: Gsk3 Proteins-paralogs Isoforms Expression and Localizationmentioning
confidence: 99%
“…According to this model, importins might be binding to a Pro closely spaced to a Tyr residue of the target protein, thus producing the nuclear translocation of the peptide. LdTopIB NLS3 includes the sequence of 218-SKINYIDPR-226, where Tyr-222 and Pro-225 are found close together [34]. …”
Section: Discussionmentioning
confidence: 99%
“…400 μl of binding buffer was added to each tube. Within 1 hr, FACS was performed on a Coulter Epics Elite equipped with a gated amplifier and upgraded with enhanced system performance in The Core Facility of Chungbuk National University [21]. …”
Section: Materials and Methodologymentioning
confidence: 99%